Enhancing Human Resource Competence through Informative Communication Techniques by North Sumatra Election Supervisory Body for Preventing 2024 Election Violations - Ramadhani, Ahmad; Kustiawan, Winda (Golden Ratio of Human Resource Management, 2024)
This study aims to analyze the implementation of the Informative Communication Technique of the North Sumatra Election Supervisory Agency in Socializing the Prevention of Election Violations 2024. This type of research is included in field research with a qualitative approach. Data collection was carried out through observation and interviews with relevant parties in Bawaslu North Sumatera. The data obtained were analyzed descriptively and interpretatively with a focus on explanations in the form of words, although there were some quantitative data that were analyzed qualitatively. The results showed that the informative communication techniques applied by Bawaslu North Sumatra were successful. There was a significant increase in public understanding of election regulations, marked by a decrease in the number of campaign violations and increased participation in reporting violations. In addition, the training and workshops conducted for political parties succeeded in increasing their level of compliance with election regulations. These communication techniques also reflect the principles of honesty, transparency and responsibility in accordance with Islamic teachings, making the electoral process more fair and democratic.